Development and Feasibility Testing of the Clinical-Community Linkage Self-Assessment Survey for Community Organizations - Fishleder, Sarah; Harris, Jeffrey R.; Petrescu-Prahova, Miruna; Kohn, Marlana; Helfrich, Christian D. (Frontiers in Public Health, 2022)
Introduction: Clinical-community linkages (CCLs) can improve health, but few instruments exist to evaluate these partnerships. To address this gap, we develop and test the Clinical-Community Linkage Self-Assessment Survey (CCL Self-Assessment). Materials and Methods: We built on an existing framework and conducted a literature review to guide the design of our survey, and obtained feedback from academic, clinical, and community-based experts. To pretest the instrument, we conducted 10 think-aloud interviews with community-based health-promotion organizations. We performed feasibility testing with 38 staff from 20 community organizations, followed by criterion-validity testing. Results: The 15-item final instrument includes five domains: Nature of the Relationship, Communication, Referral Process, Feedback Loop, and Timeliness. Expert feedback included keeping the CCL Self-Assessment brief and actionable. Think-aloud interviews produced a range of revisions related to item wording, instructions, brevity, and formatting. Feasibility testing showed high response rate and ease of administration. Sites scoring high on the CCL Self-Assessment also scored high on the criterion measure. Discussion: We demonstrate feasibility, as well as face, content, construct, and criterion validity. Initial results suggest the CCL Self-Assessment survey may be used by community organizations to identify strengths and weaknesses of their linkages. Next steps include additional statistical validation and testing to determine how the CCL Self-Assessment survey works in the field as well as providing specific tools to improve linkages.